The Politics of Passion : Norman Bethune's Writing and Art - Bethune, Norman (Book collections on Project MUSE., 1998)
"The Politics of Passion is the first comprehensive collection of the writing and art of Dr. Norman Bethune. A Canadian medical pioneer and a communist, Bethune gained fame during the 1930s while serving in the Spanish Civil War and participating in China's struggle against Japanese invasion." "This collection of Bethune's writing and art reveals that politics preoccupied him only during the last four years of his life. Earlier, his passionate nature found expression in medical and surgical innovation, as well as in painting and sketching, photography, writing (from poetry and short stories to letters, radio broadcasts, and plays), and public speaking. The Politics of Passion reveals the many facets of Bethune's identity, exploring the life not only of the revolutionary doctor, but of the intense and compassionate artist as well."--Jacket